2017
DOI: 10.1073/pnas.1621425114
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-10a is crucial for endothelial response to different flow patterns via interaction of retinoid acid receptors and histone deacetylases

Abstract: Histone deacetylases (HDACs) and microRNAs (miRs) have emerged as two important epigenetic factors in the regulation of vascular physiology. This study aimed to elucidate the relationship between HDACs and miRs in the hemodynamic modulation of endothelial cell (EC) dysfunction. We found that miR-10a has the lowest expression among all examined shear-responsive miRs in ECs under oscillatory shear stress (OS), and a relatively high expression under pulsatile shear stress (PS). PS and OS alter EC miR-10a expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
64
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 21 publications
6
64
0
Order By: Relevance
“…Our scRNAseq and scATACseq results are consistent with our previous gene array results using the endothelial-enriched RNA samples in bulk obtained from the same mouse PCL model . As shown in our bulk RNA data and other reports (Ajami et al, 2017;Jiang et al, 2014;Lee et al, 2017;Ni et al, 2010;Son et al, 2013;Wang et al, 2016;Wang et al, 2006), our singlecell data showed expected changes in many well-known flow sensitive genes including Klf2, Klf4,Nos3,Klk10,Angpt2,Ctgf,Bmp4,Timp3,Tgfb1,Thsp1,Col1a1,Tagln,Acta2,Cnn1,and Snai1. The current study also showed that d-flow induced inflammatory and proliferative pathways, consistent with our bulk RNA array result (Ni et al, 2010), further demonstrating the validity of our single-cell results. One of the major limitations of the bulk RNA study was the inability to ascertain the cell-types where the gene changes were occurring.…”
Section: Accessibility and Co-accessibility Analyses Reveal Flow-depesupporting
confidence: 89%
“…Our scRNAseq and scATACseq results are consistent with our previous gene array results using the endothelial-enriched RNA samples in bulk obtained from the same mouse PCL model . As shown in our bulk RNA data and other reports (Ajami et al, 2017;Jiang et al, 2014;Lee et al, 2017;Ni et al, 2010;Son et al, 2013;Wang et al, 2016;Wang et al, 2006), our singlecell data showed expected changes in many well-known flow sensitive genes including Klf2, Klf4,Nos3,Klk10,Angpt2,Ctgf,Bmp4,Timp3,Tgfb1,Thsp1,Col1a1,Tagln,Acta2,Cnn1,and Snai1. The current study also showed that d-flow induced inflammatory and proliferative pathways, consistent with our bulk RNA array result (Ni et al, 2010), further demonstrating the validity of our single-cell results. One of the major limitations of the bulk RNA study was the inability to ascertain the cell-types where the gene changes were occurring.…”
Section: Accessibility and Co-accessibility Analyses Reveal Flow-depesupporting
confidence: 89%
“…Based on the integrated miRNA and mRNA analysis together with target prediction and the importance of the TH signaling pathway during metamorphosis, a network of differentially expressed miRNAs and differentially expressed genes in the TH pathway was constructed. The expression of miR-10a was switched on by RARα , a hormone receptor modulated by RXRα [ 60 ]. Because RXRα and TRα were upregulated by T3 during metamorphosis and TRα was the target gene of miR-10a, T3- RXRα-RARα- miR-10a- TRα played the negative feedback role in M. fissipes metamorphosis.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, PS induces the expression, nuclear localization, and association of RAR-a with the binding enhancer retinoid X receptor-a, to augment the RAR-a binding to RARE and hence miR-10a expression. In contrast, OS induces the association of RAR-a with histone deacetylases HDAC-3/5/7, which impairs the RARa-directed miR-10a expression (35). In cultured human aortic endothelial cells, miR-10a impairs NF-kB-mediated expression of E-selectin, VCAM-1, MCP-1, IL-6, and IL-8 through targeting 2 key regulators of IkB-a degradation: TAK1 and b-TRC (33).…”
Section: Mirnas Target the Cytoplasmic Axis Of The Nf-kb Pathwaymentioning
confidence: 98%